An energy concerving modification of numerical methods for the integration of equations of motion - Robert A. Labudde; Donald Greenspan (International Journal of Mathematics and Mathematical Sciences)
In the integration of the equations of motion of a system of particles, conventional numerical methods generate an error in the total energy of the same order as the truncation error. A simple modification of these methods is described, which results in exact conservation of the energy.